2015
DOI: 10.1016/j.fertnstert.2014.12.118
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following 24-chromosome preimplantation genetic diagnosis in couples with balanced reciprocal or Robertsonian translocations

Abstract: IVF-PGD for translocation and aneuploidy screening had good clinical outcomes. Patients carrying a balanced translocation who are considering IVF-PGD should be aware of the high risk of no ET, particularly in women ≥35 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
6
28
0
Order By: Relevance
“…Technological improvements in genetic platforms used for PGS have further enhanced live birth rates along with a decrease in miscarriage rates (Brezina et al, 2016). Furthermore, carrying out PGS in addition to preimplantation genetic diagnosis (PGD) in couples with single gene disorders (Goldman et al, 2016) or translocations (Idowu et al, 2015) may enhance pregnancy outcome. Not all euploid embryos implant, however, owing to embryonic, endometrial factors, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Technological improvements in genetic platforms used for PGS have further enhanced live birth rates along with a decrease in miscarriage rates (Brezina et al, 2016). Furthermore, carrying out PGS in addition to preimplantation genetic diagnosis (PGD) in couples with single gene disorders (Goldman et al, 2016) or translocations (Idowu et al, 2015) may enhance pregnancy outcome. Not all euploid embryos implant, however, owing to embryonic, endometrial factors, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy rate is highly influencedby women׳s age. It is thought that advanced maternal age and two cell biopsies from day3 embryosare the primary reason for lower pregnancy rates following PGD for monogenic diseases in Japan.The miscarriage rate after PGD for monogenic diseases (44%, 8/18) and chromosomal abnormalities (36%,36/101) was higher than other reports [3, 16, 17]. We speculated that this high miscarriage rate was due to advanced maternal age.…”
Section: Discussionmentioning
confidence: 64%
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%